Legal Study of Cyber Phishing Crimes Using Cyber Crime Legislation in Indonesia - Asep Wedotomo; Sinarianda Kurnia Hartantien; Imam Suroso; Juli Nurani (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
The rapid development of information technology has led to the emergence of various forms of cyber crime, one of which is cyber phishing. However, Indonesian criminal law has not specifically regulated phishing as a distinct criminal offense, resulting in legal ambiguity and challenges in law enforcement. This study aims to analysis legal study of cyber phishing crimes using cyber crime legislation in Indonesia. This research employs a normative juridical method using a statutory and conceptual approach. The data used are secondary data consisting of primary, secondary, and tertiary legal materials collected through library research and analyzed qualitatively. The findings indicate that current regulations, particularly the Law on Information and Electronic Transactions (ITE Law), do not explicitly and comprehensively regulate cyber phishing, leading to uncertainty in its application. In addition, legal protection for victims remains limited, as the law primarily focuses on punishing offenders rather than providing effective compensation mechanisms. Furthermore, the new Criminal Code (Law No. 1 of 2023) has not accommodated phishing-related offenses involving personal data misuse. Therefore, legal reform is necessary to formulate clear provisions on cyber phishing and strengthen victim protection to ensure legal certainty and justice in the digital era.